2010
DOI: 10.1245/s10434-010-1141-x
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy for Papillary Thyroid Cancer: 12 Years of Experience at a Single Institution

Abstract: Sentinel lymphadenectomy for papillary thyroid carcinoma is feasible, safe, and can identify patients who may benefit from central neck dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 32 publications
0
30
1
Order By: Relevance
“…The incidence of lymph node metastases has been reported to be as high as 90% and the incidence of palpable disease ranges between 30-50% (Dixon et al, 2000;Grodski et al, 2007). Histological evidence of nodal metastases in patients with clinically node negative PTC is approximately 50% (Balasubramanian & Harrison, 2011), but rates anywhere between 25 to 90% have been reported in studies where elective neck dissections were performed on patients without suspicious lymphadenopathies (Cunningham et al, 2010). Interestingly, in a similar group of patients who were observed and did not undergo a neck dissection, the rate of recurrence was only 1.4%, thus questioning the clinical significance of such lymph node metastases (Kelemen et al, 1998).…”
Section: Lymph Nodes Metastases In Well-differentiated Thyroid Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…The incidence of lymph node metastases has been reported to be as high as 90% and the incidence of palpable disease ranges between 30-50% (Dixon et al, 2000;Grodski et al, 2007). Histological evidence of nodal metastases in patients with clinically node negative PTC is approximately 50% (Balasubramanian & Harrison, 2011), but rates anywhere between 25 to 90% have been reported in studies where elective neck dissections were performed on patients without suspicious lymphadenopathies (Cunningham et al, 2010). Interestingly, in a similar group of patients who were observed and did not undergo a neck dissection, the rate of recurrence was only 1.4%, thus questioning the clinical significance of such lymph node metastases (Kelemen et al, 1998).…”
Section: Lymph Nodes Metastases In Well-differentiated Thyroid Cancermentioning
confidence: 99%
“…Notably, a control neck dissection was not carried out in all patients in both of these studies, and as such, positive and negative predictive values could not be determined. In a recent study, Cunningham et al (2010) performed a retrospective review of 211 patients and concluded that SLNB is feasible, safe and can identify patients who may benefit from CCND. As in the other previous studies, however, a CCND was not performed on all patients and thus a false negative rate could not be determined.…”
Section: Review Of Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, more recent reports have shown that information on pathological nodal status may lead to a more personalized approach to adjuvant radioactive iodine treatment [65,66], and in this respect, accurate staging using sentinel node biopsy may provide an advantage as compared with routine elective neck dissection with regard to recurrent nerve paralysis and hypoparathyroidism. The technique has been shown to be feasible using blue dye and nanocolloid particles, with localization rates from 91 to 99% [67,68]. Pelizzo et al [68] have also shown a signiWcant diVerence in postoperative and postablation thyroglobulin levels in patients staged pN0(sn) versus pN1(sn).…”
Section: Sentinel Node Biopsymentioning
confidence: 99%